Cutaneous lasers and skin camouflage make-up: A useful alternative intervention for periorbital hairy congenital melanocytic naevus. Issue 6 (December 2013) - Townley, William A.; Bragg, Thomas W. H.; Wright, Philip A.; Cole, Richard P.
Abstract: Periorbital congenital melanocytic naevi can be very disfiguring and difficult to treat effectively. Although surgical excision and reconstruction is the most widely accepted treatment strategy, we describe a case in which cutaneous lasers treatment followed by the application of cosmetic skin camouflage make-up provided an alternative solution delivering a good cosmetic improvement.